Unveiling the Ideal Learning Methods for Kinesthetic and Visual Learners - Abdulkhayeva Laylo Alimardon qizi; Qochqorova Zulfizar Abduxamid qizi (Journal of Innovation in Education and Social Research, 2023)
This article provides a comprehensive insight into the distinct learning preferences and ideal learning methods for kinesthetic and visual learners. Within educational contexts, these two learning styles have profound implications for the delivery of effective instruction. The discussion explores the unique characteristics of each learning style and offers practical teaching strategies to optimize learning outcomes for kinesthetic and visual learners.